Effects of effluent organic matter (EfOM) on the removal of emerging contaminants by ozonation. (May 2016) - Cai, Ming-Jhih; Lin, Yi-Pin
Abstract: Removal of emerging contaminants in wastewater treatment is essential to ensure the ecological health of the receiving water bodies. Ozonation is a promising technology to achieve this purpose but important wastewater characteristics affecting the optimal removal efficiency need to be elucidated. Secondary effluents contain effluent organic matter (EfOM), which can react directly with ozone as well as react as the initiator, promoter and inhibitor in the hydroxyl radical (.OH) chain reactions resulting from ozone decomposition. These different reaction modes of EfOM, coupled with alkalinity and pH value, collectively determine the ozone and .OH exposures and the degradation of pharmaceutical compounds by ozonation. In this study, we determined the rate constants of EfOM collected from two municipal wastewater treatment plants in terms of direct ozone reaction, initiation, promotion and inhibition at various pH values (pH 6.0–7.5) and temperatures (10–30 °C). The rate constants of direct reaction and initiation generally increased with the increasing pH value while the rate constants of promotion and inhibition did not vary significantly. All rate constants increased with the increasing temperature. The removal of ibuprofen, acetylsulfamethoxazole and metoprolol in diluted secondary effluent by ozonation can be fairly-well modeled by using the determined rate constants of EfOM. Graphical abstract: Highlights: Rate constants of different reaction modes of EfOM in ozonation were determined. Effects of pH value and temperature on these rate constants were investigated. Influences of EfOM on the removal of three pharmaceuticals were evaluated and modeled.